Application of remote sensing and GIS for assessing the level of change of land use status in the coast of Ngoc Hien district (Ca Mau province) due to the impact of sea level rise - Hong, Pham Viet; Tuan, Tran Anh; Nguyet, Nguyen Thi Anh (Vietnam Journal of Marine Science and Technology, 2019)
Today, environmental hazards and challenges are no longer confined to the national or regional scale but on the global scale. One of the biggest challenges for humanity is the natural disasters, global warming and sea level rise. The natural disasters causing serious consequences for human life, such as: Storms, floods, earthquakes, tsunamis, desertification, high tides... increase in frequency, intensity and scale. In recent years, Ca Mau province as well as coastal provinces of Vietnam is under great influence due to the impacts of climate change. One of the most affected districts in Ca Mau province is Ngoc Hien district. The district has a geographic location with three sides bordering the sea, one side bordering the river, a completely isolated terrain. The terrain is flat, strongly divided by the system of natural rivers and canals and intertwined canals, so it is constantly flooded by the sea. Ngoc Hien district is characterized by a sub-equatorial monsoon climate, directly affected by irregular semi-diurnal regime. The main purpose of the paper is to assess coastal vulnerability due to the impact of climate change over time with GIS-based remote sensing images. Remote sensing data with multi-time characteristics, collected in many periods and covering a wide area is an effective tool for monitoring shoreline fluctuations in particular and land use status of the study area in general.